The role of journalism in the formation of ecological consciousness of society - Uikasbayeva А.Б.; Kurmanbayeva А.Ә. (Bulletin of L.N. Gumilyov Eurasian National University. JOURNALISM Series, 2022)
The article first gives an overview of the general term environmental journalism and then explains related concepts such as «environmental literacy,» «environmental awareness,» «environmental culture,» and «environmental education».How these concepts are formed in human consciousness is discussed in detail. The role of mass media in the formation of public ecological consciousness is widely discussed. It is not enough for a person to know basic facts and data about ecology in order to have compassion for nature and be responsible in their relationship with the environment. To do so, people need to be informed daily through a variety of sources about how much and how our geographic environment is changing. There is also a need for accurate information about the causes of environmental change in today’s society. Such materials lead to environmental literacy and the prevention and solution of some environmental problems. In turn, one of the main functions of the media is to broadly analyze, publish, distribute, and disseminate materials of this nature. Thus, it became clear that every quality content of environmental character published in the media has a great role in the formation of environmental consciousness of the population. The article demonstrates this advantage of environmental journalism. The article also points out that the media has shortcomings in providing information about our environment. In general, it is proved that the media has a direct impact on the environmental literacy, culture and consciousness of citizens.